Peran personal branding dalam pengembangan karir generasi Z: Kajian literatur sistematik - Salean, Marla; Manafe, Yuni Maharani; Malihing, Rossaliani; Bessie, Jesica Solagrasia (Universitas Muhammadiyah Malang, 2026)
The rapid growth of digital technology has changed how careers are developed, especially for Generation Z who are active users of digitalmedia. Competition in the job market requires Generation Z to find effective ways to stand out, one of which is personal branding. This topicwas chosen because personal branding is increasingly important in the digital era, yet studies focusing on its role in Generation Z careerdevelopment are still limited. This study assumes that personal branding has a positive role in supporting the career development ofGeneration Z. A systematic literature review was conducted using the PRISMA-P 2015 guidelines. Data were collected from ERIC andGoogle Scholar database, covering peer-reviewed articles published between 2020 and 2025 using qualitative and quantitative methods.From 517 identified articles, three studies met the inclusion criteria and were reviewed. The results show that personal branding helps Generation Z build a professional identity, increase self-confidence, expand professional networks, and improve career opportunities. Social media use, digital skills, personal values, and professional platforms such as LinkedIn support the development of personal branding. In conclusion, personal branding plays an important role in enhancing career readiness and competitiveness of Generation Z in the digital era.